Gold in the sun [large type] - Richards, Dusty (THORNDIKE PRESS LARGE PRINT softcover Western, 2024)
"A drunken plan to make some quick money with two friends landed drifter Whit Ralston in the Yuma Territorial Prison-the worst prison in Arizona. Now he's doing hard time in the inferno the inmates call the Hell Hole, counting the days until his release. He's vowed never to do anything so stupid again... but then his crazy cellmate, Ratero, starts talking about a load of stolen gold stashed up in the mountains. At first, Whit dismisses it as fantasy, the feverish rantings of a man who'd spent too many years in stir. Then he's furloughed to help with a construction project outside the prison. The taste of freedom is intoxicating, but everyone he meets wants to know just one thing-where's Cordova's gold? Could Ratero's rantings possibly be based in truth? Could the gold really exist? When he falls for a beautiful, blue-eyed lady of the evening who seems as taken with him as he with her, Whit realizes he might have a new reason to run some risks. Once he gets out of prison, Whit starts making plans-but he's going to have to make better choices about just who to believe in order to hit pay dirt. People say a lot of things, but when it's money on the line, your best friend today could be holding you at gunpoint tomorrow. In the Old West, though, following the law is never as important as trusting the right people"--